Flow pattern and rheology of marine ice from Nansen Ice Shelf, Antarctica: constraints for modeling - Samyn, Denis; Remy, Jean-Philippe; Duval, Paul; Montagnat, Maurine; Tison, Jean-Louis (2007)
info:eu-repo/semantics/published